Integration of digital technology by health analysts in health information systems: Systematic Review - Suprapto Suprapto; Muh Ihsan Kamaruddin (Edukasi Ilmiah Indonesia, 2025)
Introduction: The rapid advancement of digital technology has significantly transformed health information systems (HIS) worldwide. Health analysts, as key professionals in managing health data, play a crucial role in the integration and utilization of these digital tools. However, the extent, effectiveness, and challenges of this integration remain underexplored across different healthcare contexts. This systematic review aims to examine the integration of digital technology by health analysts within health information systems, focusing on the types of technologies adopted, the roles played by health analysts, the benefits gained, and the challenges encountered during implementation. Methods: Following the PRISMA 2020 guidelines, we conducted a systematic search of peer-reviewed articles published between 2013 and 2025 from databases including PubMed, Scopus, ScienceDirect, and Google Scholar. Keywords used included “health analyst”, “digital technology”, “health information system”, and “integration”. Eligible studies included primary research involving health analysts and the application of digital health technologies. Results: From an initial pool of 1,274 articles, 28 studies met the inclusion criteria. The findings reveal that health analysts have been instrumental in integrating technologies such as Electronic Health Records (EHR), Laboratory Information Systems (LIS), data analytics platforms, and mobile health applications. The integration has led to improved data accuracy, faster reporting, and enhanced decision-making support. Nonetheless, several challenges were identified, including lack of digital training, infrastructure limitations, and regulatory gaps. Conclusions: The integration of digital technologies by health analysts significantly enhances the performance of health information systems. However, successful adoption requires continuous professional development, supportive policies, and robust digital infrastructure. Future efforts should focus on strengthening the digital competencies of health analysts and aligning technology integration with national health strategies.